2022
DOI: 10.1111/joss.12777
|View full text |Cite
|
Sign up to set email alerts
|

Color‐nutrient associations: Implications for product design of dietary supplements

Abstract: Dietary supplements are prevalent and represent a huge (and still growing) global market. Such products are intended to enhance health and wellness as well as to supplement diets. Compared to the large amount of dietary supplements research on nutrition, dietetics, and medicine, far less research has been conducted in the realm of sensory and consumer science. Product design is undoubtedly an important element of any brand's success, no matter what the category, and can be used to convey various symbolic meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Supplement color preferences are yellow, maroon, gray, and brown, in that order from most to least preferred 27 . Furthermore, according to other studies, people tend to think or believe that the colors of vitamin supplements are yellow (47%) and orange (39%), or colors with a tendency to be light 28 . Based on this, it could be concluded that the pale brown color of MMS was considered less attractive because it did not conform to pregnant women's expectations about the color of vitamins.…”
Section: Factors Associated With the Consumption Adherence Of Ifa And...mentioning
confidence: 99%
“…Supplement color preferences are yellow, maroon, gray, and brown, in that order from most to least preferred 27 . Furthermore, according to other studies, people tend to think or believe that the colors of vitamin supplements are yellow (47%) and orange (39%), or colors with a tendency to be light 28 . Based on this, it could be concluded that the pale brown color of MMS was considered less attractive because it did not conform to pregnant women's expectations about the color of vitamins.…”
Section: Factors Associated With the Consumption Adherence Of Ifa And...mentioning
confidence: 99%
“…Several product-related design elements are usually involved in the process of product design [12]. Considering all the design elements of a product and selecting the best design solution has a crucial impact on the product's market share and user satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%